PENGARUH PEMBELAJARAN ONLINE TERHADAP MINAT BELAJAR PADA MAHASISWA PGSD STKIP INVADA CIREBON - Mochamad Guntur; Elsa Damayanti (PERISKOP : Jurnal Sains dan Ilmu Pendidikan, 2021)
This study aims to determine the relationship between interest in learning and learning outcomes in online lecture learning in the primary school teacher education department at STKIP INVADA University Cirebon. In addition, this research is also to develop technological media in the form of blogs, whatsapp, google classroom, zoom, and other learning media to determine the effect of supporting online learning on students. The population of this study is elementary school teacher education students with online learning majors. There are 21 elementary school teacher education students at the STKIP INVADA University Cirebon. Data collection techniques using questionnaires or questionnaires, interviews and documentation methods. The questionnaire method was used to reveal the variables of student interest in learning, interviews were used to strengthen the questionnaire method in knowing student answers about student interest in learning in online learning in accordance with actual conditions, and the documentation method was used to reveal data on online learning outcomes. The instrument validity test uses Product Moment correlation, and the reliability test uses Cronbach's Alpha formula with the number of respondents N = 13 for students of the PGSD study program class of 2021 and 2022. The analysis prerequisite test consists of normality test, homogeneity test. The results of this study indicate that there is a significant relationship between the relationship of interest in learning to learning outcomes in students of the primary school teacher education study program at STKIP INVADA Cirebon, with = 0.570; r2 = 0.3249 and 5.237 is greater than 1.672 with a significance of 0.000.